2017
DOI: 10.1002/biot.201700168
|View full text |Cite
|
Sign up to set email alerts
|

High‐yield production of recombinant CRM197, a non‐toxic mutant of diphtheria toxin, in the periplasm of Escherichia coli

Abstract: A high cell density fed-batch process was developed for production of recombinant CRM197, a non-toxic mutant of diphtheria toxin widely used as a carrier in polysaccharide-protein conjugate vaccines. Fully soluble recombinant CRM197 was obtained in high yields and with an authentic N-terminus, by targeting the protein to the periplasm of Escherichia coli using the Signal Recognition Particle (SRP)-dependent signal sequence of FlgI. Response Surface Methodology (RSM) was used to optimize the set-points of key p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Production of CRM 197 is hindered, however, by the strict growth requirements of the traditional expression system (C diphtheriae) and generally lower yields compared to other expression systems. 8 Given these challenges, the evaluation of recombinant CRM 197 expressed in multiple heterologous organisms (e.g., E coli, P fluorescens, Bacillus subtilis) is being pursued as an alternative source of carrier proteins. 9 Given the complex process of manufacturing conjugate vaccines, 10 delineating the physicochemical properties of recombinant CRM 197 , expressed in C diphtheriae or a heterologous system, is essential to mitigate risk during manufacturing, including subsequent polysaccharide conjugation, to ensure the immunogenicity of the final drug product.…”
Section: Introductionmentioning
confidence: 99%
“…Production of CRM 197 is hindered, however, by the strict growth requirements of the traditional expression system (C diphtheriae) and generally lower yields compared to other expression systems. 8 Given these challenges, the evaluation of recombinant CRM 197 expressed in multiple heterologous organisms (e.g., E coli, P fluorescens, Bacillus subtilis) is being pursued as an alternative source of carrier proteins. 9 Given the complex process of manufacturing conjugate vaccines, 10 delineating the physicochemical properties of recombinant CRM 197 , expressed in C diphtheriae or a heterologous system, is essential to mitigate risk during manufacturing, including subsequent polysaccharide conjugation, to ensure the immunogenicity of the final drug product.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the notable result for periplasmic soluble expression of CRM197 in E . coli was reported [ 22 ]. It was reported to achieve production of 3 g/l of CRM197 by a high cell density fed-batch process.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, successful periplasmic expression of soluble CRM197 in E . coli was reported [ 22 ]. The authors showed that the purity of the primary cell extract reached 36.5% of total protein after periplasmic extraction by osmotic shock, while not exceeding 8.3% of total protein by whole cell disruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Special issue of the Biotechnology Journal , the official journal of the society, showcases some of the technical programe of the symposium and the advances and topics of interest in biochemical engineering, ranging from bioeconomy , sustainability and solvent free extractions , discovery and optimization of new biocatalysts , design of new biotherapeuticals , as well as new process control and design approaches based on modeling and predictive tools .…”
mentioning
confidence: 99%